A taxonomic study for Fumaria asepala Boiss. and Fumaria schleicheri Soy.-Will. subsp. microcarpa Boiss. ex Hausskn. growing in Turkey: evidence from morphological, anatomical and palynological studies - Sancar, Pelin Yılmaz (My University, 2022)
The genus Fumaria L. belongs to the Papaveraceae family, and consists of plants that are difficult to distinguish morphologically. In this study, it is aimed to reveal the structural features of two species belonging to the genus Fumaria. To this end, leaf, sepal, petal dimensions and shapes, filament and anther lengths, and various morphological characteristics were examined and necessary measurements were made. Within the scope of anatomic studies, cross-sections were made manually from roots and stems of species, and preparations were prepared by reverse staining technique and photographed under a light microscope to determine anatomic characteristics. Additionally, light microscope and SEM studies were made to expose pollen characteristics. According to the results of the studies, Fumaria asepala Boiss. and Fumaria schleicheri Soy.-Will. subsp. microcarpa Boiss. ex Hausskn. species live together in the area and display an interesting characteristic. Following microscopic studies, although these two species are morphologically very similar to each other, F. asepala is different from F. schleicheri subsp. microcarpa by the absence of sepal. Again, fruit micromorphologies also provide valuable data to distinguish the species. Results of anatomic studies were also similar in both species. In palynological studies that examined pollens, it was observed that pollen types were suboblate for both species, and apertures of pollens were pantoporate/porate. The number of apertures was 6-7 in F. asepala, 4-8 in F. schleicheri subsp. microcarpa, and larger in F. asepala species. Additionally, the pollens of F. schleicheri subsp. microcarpa were larger compared to F. asepala. Original data were obtained about species after combining these results, and basic systematic data about genus was brought to the literature. This study is important as it is the detailed systematic study of Fumaria species grown in Elazığ province.
Keywords: Biyoloji; Parazitoloji